2011
DOI: 10.1177/2040622311424805
|View full text |Cite
|
Sign up to set email alerts
|

New anticoagulants in atrial fibrillation: an update for clinicians

Abstract: Anticoagulation is vital for stroke and systemic embolism prevention in patients with atrial fibrillation. Current therapy with the vitamin K inhibitor warfarin has many inherent limitations in clinical practice. With the potential of broadening anticoagulation therapy to a larger population, new classes of anticoagulants have recently emerged with the potential for improved efficacy, safety and convenience. Direct thrombin inhibitor and Factor Xa inhibitor classes are showing promise for both patients and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Concerns regarding under treatment and ineffective management with warfarin have led to the development of new oral anticoagulants(NOACs). (8) Comparative trials of warfarin to the NOACs in patients with non-valvular AF (NVAF) have demonstrated the NOACs to be non-inferior (9) or slightly superior (10) to warfarin in terms of stroke and systemic embolism, and associated with lower intracranial haemorrhage rates. (9, 10) However, Gomez-Outes et al (9) demonstrated differences in outcomes according to warfarin TTR and suggested a trend towards superiority of the NOACs in centres with TTR<65%.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns regarding under treatment and ineffective management with warfarin have led to the development of new oral anticoagulants(NOACs). (8) Comparative trials of warfarin to the NOACs in patients with non-valvular AF (NVAF) have demonstrated the NOACs to be non-inferior (9) or slightly superior (10) to warfarin in terms of stroke and systemic embolism, and associated with lower intracranial haemorrhage rates. (9, 10) However, Gomez-Outes et al (9) demonstrated differences in outcomes according to warfarin TTR and suggested a trend towards superiority of the NOACs in centres with TTR<65%.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining INR values within the range of 2.0-3.0 optimises the benefit to risk ratio of warfarin treatment, 5 with time in therapeutic range (TTR) a recommended measure for quality of warfarin management. 6 A TTR minimum target threshold of 60% is recommended to ensure benefit from warfarin, 7 with poor control (TTR < 60%) associated with higher mortality, major bleeding and systemic embolism events in patients treated with warfarin. 8 The introduction of newer oral anticoagulants (NOAC), which act as direct thrombin inhibitors or factor Xa inhibitors, has potentially simplified anticoagulation, with these agents demonstrating fixed dosing and less monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining INR values within the range of 2.0–3.0 optimises the benefit to risk ratio of warfarin treatment, with time in therapeutic range (TTR) a recommended measure for quality of warfarin management . A TTR minimum target threshold of 60% is recommended to ensure benefit from warfarin, with poor control (TTR < 60%) associated with higher mortality, major bleeding and systemic embolism events in patients treated with warfarin …”
Section: Introductionmentioning
confidence: 99%
“…69 Given the more reliable composition of Prothrombin complex concentrates (PCCs), and greater concentration of thrombin and factor X, PCCs may be preferred over Fresh Frozen Plasma (FFP) or recombinant Factor VII a (rF-VIIa). 70 Since heparinoids, hirudin-like agents and dabigatran possess relatively low or no protein binding, as opposed to other direct or indirect thrombin and factor Xa inhibitors, hemorrhage in conjunction with these agents may theoretically be more likely to respond to serologic extraction by dialysis. 71 Although not well studied, dialysis may also clear the direct factor Xa or thrombin inhibitors, all of which are small molecules.…”
Section: Potential Drawbacks Of New Anticoagulantsmentioning
confidence: 99%